2013
DOI: 10.1371/journal.pone.0068086
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Wavelength UV Photofunctionalization on Micro-Arc Oxidized Titanium

Abstract: Many challenges exist in improving early osseointegration, one of the most critical factors in the long-term clinical success of dental implants. Recently, ultraviolet (UV) light-mediated photofunctionalization of titanium as a new potential surface treatment has aroused great interest. This study examines the bioactivity of titanium surfaces treated with UV light of different wavelengths and the underlying associated mechanism. Micro-arc oxidation (MAO) titanium samples were pretreated with UVA light (peak wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 42 publications
4
54
0
Order By: Relevance
“…Hydrophilic contact angles are typically defined as those ≤90°, and superhydrophilic contact angles are defined as those below 5° showing near perfect wetting . Previous studies have shown increased hydrophilicity of photofunctionalized titanium and titanium oxide surfaces upon UVA or UVC irradiation . However, the ability of UVA and UVC treatments to produce superhydrophilicity in titanium oxides remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrophilic contact angles are typically defined as those ≤90°, and superhydrophilic contact angles are defined as those below 5° showing near perfect wetting . Previous studies have shown increased hydrophilicity of photofunctionalized titanium and titanium oxide surfaces upon UVA or UVC irradiation . However, the ability of UVA and UVC treatments to produce superhydrophilicity in titanium oxides remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Low power laser and UV may be effective in treating periimplantitis (45,46). 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 Zirconia is zirconium oxide (ZiO) and is not considered to be biologically active (48,49). The UV may be effective in surface treatment because it may reach most, if not all, of the rough surface due to reflection off of the titanium surface irregularities.…”
Section: Uv and Peri-implantitismentioning
confidence: 99%
“…The UV treatment converted the ZiO surface from being hydrophobic to hydrophilic (48,49). The UV treatment converted the ZiO surface from being hydrophobic to hydrophilic (48,49).…”
Section: Uv and Zirconiamentioning
confidence: 99%
“…UVA or UVC, and illumination times. Gao et al 16 recently reported higher cell proliferation on micro-arc oxidized titanium irradiated by UVC light (superhydrophilic) rather than by UVA light (hydrophilic) if 24 h irradiation was used. They assumed that the enhanced biological activity was due to photolytic activity (direct hydrocarbon disruption) under UVC rather than photocatalytic activity.…”
Section: Hmscs Under Osteogenic Stimulusmentioning
confidence: 99%
“…12,13 Very recently, a new phenomenon, called ''photofunctionalization'', has been revealed to occur after prolonged exposure to UVC irradiation (48 h), which promoted remarkably high cell attachment, proliferation and differentiation on titanium. 14,15 Gao et al 16 claimed that the critical aspect depends on the UV wavelength: starting from micro-arc oxidized titanium, the UVC-treated surfaces exhibited superior bioactivity than the UVA-treated ones. The authors declared that the photo-induced hydrophilicity of the TiO 2 -surfaces was achieved using UVA irradiation, while only the UVC irradiation was able to provoke a photolytic effect (direct decomposition of hydrocarbons), obtaining highly cleaned surfaces.…”
Section: Introductionmentioning
confidence: 99%